Phase-field modelling of paramagnetic austenite–ferromagnetic martensite transformation coupled with mechanics and micromagnetics. (1st March 2022) - Ohmer, Dominik; Yi, Min; Gutfleisch, Oliver; Xu, Bai-Xiang
Abstract: A three-dimensional phase-field model is proposed for simulating the magnetic martensitic phase transformation. The model considers a paramagnetic cubic austenite to ferromagnetic tetragonal martensite transition, as it occurs in magnetic Heusler alloys like Ni 2 MnGa, and is based on a Landau 2-3-4 polynomial with temperature dependent coefficients. The paramagnetic–ferromagnetic transition is recaptured by interpolating the micromagnetic energy as a function of the order parameter for the ferroelastic domains. The model is numerically implemented in real space by finite element (FE) method. FE simulations in the martensitic state show that the model is capable to correctly recapture the ferroelastic and -magnetic microstructures, as well as the influence of external stimuli. Simulation results indicate that the paramagnetic austenite to ferromagnetic martensite transition shifts towards higher temperatures when a magnetic field or compressive stress is applied. The dependence of the phase transition temperature shift on the strength of the external stimulus is uncovered as well. Simulation of the phase transition in magnetocaloric materials is of high interest for the development of energy-efficient magnetocaloric cooling devices. Graphical abstract: Highlights: Micromagnetic phase-field model describing the martensitic transformation. Modification of micromagnetic energies to account for magnetic transitions. Simulation of field- and stress-induced martensite transformation. Stress- and field-induced shift of austenite–martensite transition temperature.